2017
DOI: 10.31768/2312-8852.2017.39(2):124-130
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Cisplatin in Human Blood Plasma and Urine Using Liquid Chromatography-Mass Spectrometry for Oncological Patients With a Variety of Fatty Tissue Mass for Prediction of Toxicity

Abstract: Aim: The research was aimed to analyze a level of triglycerides in blood serum as a possible new marker of toxicity, particularly in patients with excess body weight, receiving cisplatin. Materials and Methods: Study involved 20 oncological patients with stage III lung cancer, who received palliative treatment with cisplatin. High-performance liquid chromatography was used for quantitative determination of pure cisplatin in urine and blood samples. Cisplatin concentration of the test samples was determined bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…22,23,49 The choice of the drug dose in our study was based on the MTT-assay and a prior knowledge of concentration of cisplatin in the blood plasma of patients, which is 3 to 6 μM. 40,51 Previously, we showed that cisplatin at a concentration of 2.4 to 2.6 μM affects the proliferative ability rather than viability of cancer cells HeLa-the number of dead cells did not exceed 10%, whereas the cells growth was inhibited after 24 h exposure to cisplatin. 38 It is known that cisplatin increases the duration of S-phase and blocks cells in G2-phase of the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23,49 The choice of the drug dose in our study was based on the MTT-assay and a prior knowledge of concentration of cisplatin in the blood plasma of patients, which is 3 to 6 μM. 40,51 Previously, we showed that cisplatin at a concentration of 2.4 to 2.6 μM affects the proliferative ability rather than viability of cancer cells HeLa-the number of dead cells did not exceed 10%, whereas the cells growth was inhibited after 24 h exposure to cisplatin. 38 It is known that cisplatin increases the duration of S-phase and blocks cells in G2-phase of the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The tested concentrations of cisplatin were in the range of maximum concentrations of the drug in the blood plasma of patients, 1 to or 3 to on average. 40 The cells were incubated with the drug from 10 min to 48 h, spheroids—from 3 to 48 h, and viscosity was measured immediately after the treatment. Untreated cells or spheroids served as a control.…”
Section: Methodsmentioning
confidence: 99%
“…The higher the percentage of p-glycoprotein, the higher the cell's ability to resist the response of the given cytotoxic compound. In other words, if a low percentage of p-glycoprotein is found, then the cytotoxic ability of the drug has a positive effect on cells [11], [12], [13], [14], [15].…”
Section: Discussionmentioning
confidence: 99%
“…The p-glycoprotein substrate efflux is related to the energy consumption of ATP binding to NBD and hydrolysis. After ATP binding, ATP hydrolysis is essential for the conformational change of the p-glycoprotein from the outside to the inside that will continue the next efflux cycle [8], [9], [11], [15], [16]. This indicates that the combination of cinnamon bark extract of 68.73 ug/ ml and cisplatin of 117.5 uM has the best effect on drug efflux so that it has the potential to prevent cisplatin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, some LC methods using tandem mass spectrometry (MS/MS) determination have been developed to analyze carboplatin in plasma [ 20 ], carboplatin and oxaliplatin in surfaces [ 21 ] and cisplatin, carboplatin, and oxaliplatin in surfaces employing zwitterionic hydrophilic interaction liquid chromatography (HILIC) [ 22 ]. There are also studies that have proposed the determination of cisplatin or carboplatin indirectly through derivatization with diethyldithiocarbamate DDTC in plasma and urine [ 2 , 23 , 24 , 25 ]. Therefore, the aim of this study was to propose an analytical method for the simultaneous determination of cisplatin, carboplatin, and oxaliplatin in human urine.…”
Section: Introductionmentioning
confidence: 99%